Венозная система грудных конечностей лося (Alces alces L.) и ее клапанный аппарат. Сообщение I. Венозная система области кисти - Комаров, А.В. (Вестник зоологии, 1969)
The venous system of 10 pectorial limbs in Alces alces L. (foetuses and adult animals) was studied by means of anatomic methods of investigation. It is established that the venous blood passes from the foot by 13 magistral vanae.
The topography of the foot venae, their length and diameter are presented. Venous anastomoses are described. Volar venae are the most developed. Venae of the foot are located in grooves and under tendons and, that is why they are protected against mechanical damages. There are more valves in volar venae than in dorsal ones. The valves are grouped in twos-fours in each group.